Penerapan Kombinasi AHP-WP Pada Sistem Pendukung Keputusan Pemilihan Lokasi Pembangunan Perumahan - Rizka Putri Utami; Mujib Ridwan; Faris Mushlihul Amin (Jurnal Ilmiah Informatika, 2019)
As the age of the earth grows, so does the number of inhabitants who inhabit it. As we know, home or residence is one of the basic needs for humans. This is a very promising opportunity for housing developers, given the large number of residents, especially in Indonesia, who need housing. But there are some problems that must be faced by housing developers to choose the right place of development. One of them is the number of criteria that must be met for a place to be chosen. The purpose of this research is to facilitate and support in choosing housing construction locations. Decision Support System to be the right solution because complex calculations can be computerized to make it easier. Housing selection criteria are obtained based on interviews with PT Metro Perkasa Abadi for further processing. AHP and WP methods are suitable methods to be combined in solving existing problems. The AHP results are criteria weights, while WP generates location rankings.